Case report of old anterior dislocation of the shoulder joint and review of the literature - Guo, Weiming; Hui, Ming; Yang, Yuan; Wan, Teng; Zeng, Guang-Gui; Huang, Peiguan; Wang, Xiaoxu; Qiu, Mingjun (Frontiers in Surgery, 2022)
Abstract Background: anterior dislocation of shoulder is the most common dislocation of joint. With the improvement of diagnosis rate, the clinical diagnosis of old anterior dislocation of shoulder is relatively rare. This year, with the improvement of arthroscopic technology, arthroscopic treatment is the mainstream way of shoulder dislocation. However, the current treatment plan for old anterior shoulder dislocation is not clear, and arthroscopic treatment may be difficult to reduce. Case report: this paper reports the clinical experience of arthroscopic treatment of traumatic old anterior shoulder dislocation in a 30-year-old woman. After follow-up for 6 months, regular postoperative reexamination and early rehabilitation training were conducted. There were no postoperative complications, excellent score according to Rowe and Zarin criteria, competent for daily activities, no pain, 10 °loss of anterior lift, 30 °loss of external rotation, and average loss of 1 vertebral body level of internal rotation. Conclusion: arthroscopic release and repair is an alternative option for the treatment of old anterior shoulder dislocations.